Urban Middle-Class and the Politics of Home Ownership in South Korea - Kim, Myeongsoo (Journal of Asian sociology, 2018)
This study explores the changing functions of home ownership in the livelihood of the urban middle class. Home ownership has long served as a strong motivational mechanism for integrating private subjects by creating material rewards expectations and desire for status achievement. Although social aspirations for popular ownership of owner-occupied house have sprung up during the transition to democracy, such demands have gradually disappeared with the selective incorporation as homeowners. Since the financial crisis of 1997, the function of home ownership has extended beyond the guarantees of economic security to an exclusive means of survival. The recent decline of social solidarity in the urban middle-class lifestyle is observed in the territory formation strategy that pursues capital gains, and conservative ownership politics. This study concludes that privatized housing practices by home owners represents the pattern of life politics of the urban middle class in Korea today.